Modelling and fabrication of cylinder head for single cylinder two stroke engine - Abdul Hadi, Abd Majid (2007)
Automotive technology is very important to people nowadays. To help them to move someplace to other place in short time. Automotive technology is very fast growing because of their needed in human life. The two stroke engine is reciprocating engine in which the piston takes over any valve functions in order to obtain power stroke each revolution of the crankshaft. This involves the use of ports in the cylinder walls which are covered and uncovered by movements of piston. Two stroke engines are used for motorcycles, lawn mowers, chain saw and marine engine. Cylinder Head is one of the important parts in engine part. The purpose of The Cylinder Head to cover the movement of piston from Bottom Dead Centre to Top Dead Centre and also combustion chamber in The Cylinder Head is very important in combustion process.